The phylogenetic relationships of the two-winged South American Leptophlebiidae genera revisited with first description of the male imago of Bessierus Thomas & Orth (Insecta: Ephemeroptera) - Domínguez, Eduardo; Cuezzo, María Gabriela; Clavier, Simón (Zootaxa, 2019)
Four of the 43 genera of South American Leptophlebiidae are dipterous. A previous phylogenetic hypothesis supported that clade Askola+Hagenulopsis, and that Bessierus+Perissophlebiodes, are sister groups of the Farrodes complex. Adults of Bessierus and Perissophlebiodes were not known but posteriorly Perissophlebiodes male imago was described. Here, we describe the male imago of Bessierus for the first time. Both genera share, besides the absence of the hind wings, the asymmetrical fork of MA, symmetrical fork of MP, dissimilar tarsal claws, and forceps sockets fused. Along with the description of the imago, a new diagnosis for the genus Bessierus is presented, also updating the identification key with this new information. A new cladistics analysis is performed to test the stability of the proposed relationships of these four genera within Leptophlebiidae. We obtained a single cladistic hypothesis where the addition of Bessierus adult characters resulted in new synapomorphies for the (Bessierus, Perissophlebiodes) clade, and improved its clade statistical support. The fused forceps sockets resulted in a synapomorphy uniting Bessierus, Perissophlebiodes and Simothraulopsis. As a result of this new analysis, the hypothesis of independent losses of the hind wings in the two dipterous groups studied is supported. The Farrodes lineage is not supported as proposed in previous studies, being restricted only to (Farrodes (Simothraulopsis, Homothraulus)) while the identity of “Perissophlebiodes lineage” is supported. The sister group relationship of Rondophlebia is not clearly defined.